THE EFFECT OF SLIMMING HERBS TEA WITH DIETARY ADJUSTMENT TO THE RESULT OF ANTROPOMETRIC MEASUREMENT AMONG WOMEN MEMBER OF AEROBIC STUDIO - Perslami, Resti; Puruhito, Edith Frederika; Agil, Mangestuti (Journal of Vocational Health Studies, 2017)
Background: Overweight is the accumulation of excessive fat that can harm health. People who are overweight usually have a size of body anthropometry more than normal, such as the size of the waist circumference (WC), upper arm circumference (UAC), and subcutaneous fat thickness (SFT). Women are more to being overweight, because metabolism in women is lower and body fat is more than men. They attempt to return to normal body weight, by following the fitness clubs, diet and so forth. In this study, researchers used a slimming herbs tea to help restore their body size. Purpose: This study was to determine the effects of slimming herbs tea with dietary adjustments to the results of anthropometric measurements in the group of gymnastic class women. Method: The method used is quasy experimental design with the design of "pre-posttest control group design”. The study was held for 14 days by the number of respondents 14 people. Respondents were divided into 2 groups: control and treatment (consumption of slimming herbs tea). Slimming herbs tea composition consisting of green tea, guazuma extracts, parameria extract, fennel extract and curcuma extract consumed 2 times a day after meals every day. Data were analyzed using SPSS with Paired T-Test. Result: The results showed slimming herbs tea with dietary adjustments can reduce the results of anthropometric measurements such as WC as much as 6,21 cm ,UAC as much as 2,2 cm ,and SFT as much as 2,7 mm. While the reducing measurement in control group, in WC as much as 2,57 cm, UAC as much as 1,6 cm, SFT as much as 1,4 mm. Conclusion: The effect of slimming herbs tea with dietary adjustment can reducing the result of anthropometric measurement more in the woman class of gymnastic